2022
DOI: 10.47163/agrociencia.v56i4.2808
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilization for Maize Based on Attainable Yield and Soil Organic Matter Content

Abstract: Agricultural soils generally do not provide enough N to satisfy crop needs, so it is necessary to apply it as fertilizer. This supply can be estimated by chemical analysis of the soil and, based on this and the needs of the plant, nitrogen fertilization recommendations are made for the crops. The objective of this study was to determine economic optimum N rates for maize (Zea mays L.), based on attainable yield and soil organic matter content as an estimator of soil N supply, with the current and increased N/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…The relationship tends: (1) to be linear, except for attainable yield levels below 2 Mg ha -1 and from 8 to 10 Mg ha -1 under rainfed conditions that do not follow this trend; and (2) under irrigated conditions, this relationship follows a similar trend to rainfed conditions but with higher EONR and EOY values (Figure 1). This study found that the relationship between EONR and EOY is similar to those reported by Sánchez-Roldán et al (2022) in their study across 16 Mexican states, involving 67 experiments on maize response to N in soils with 2 % of organic matter.…”
Section: Economic Optimal Rate Of Nitrogen By Level Of Attainable Yieldsupporting
confidence: 83%
“…The relationship tends: (1) to be linear, except for attainable yield levels below 2 Mg ha -1 and from 8 to 10 Mg ha -1 under rainfed conditions that do not follow this trend; and (2) under irrigated conditions, this relationship follows a similar trend to rainfed conditions but with higher EONR and EOY values (Figure 1). This study found that the relationship between EONR and EOY is similar to those reported by Sánchez-Roldán et al (2022) in their study across 16 Mexican states, involving 67 experiments on maize response to N in soils with 2 % of organic matter.…”
Section: Economic Optimal Rate Of Nitrogen By Level Of Attainable Yieldsupporting
confidence: 83%